RISK FACTORS AND ESOPHAGOGASTRODUODENOSCOPY FINDINGS ON NON-STEROIDAL ANTI-INFLAMMATORY DRUGS USER AT SANGLAH HOSPITAL 2016-2018 - Magat, Renaldy Frederich Nathanael; Wibawa, I Dewa Nyoman; Somayana, Gde; Mariadi, I Ketut (E-Jurnal Medika Udayana; Vol 11 No 1 (2022): E-Jurnal Medika Udayana, 2022)
The use of non-stereoidal anti-inflammatory drugs (NSAIDs) for a certain time and dose can cause abnormalities in the digestive tract ranging from asymptomatic, ulcers, bleeding to perforation. This study aims to determine the distribution of the proportion of patients with abnormality in gastric and duodenal due to NSAIDs based on esophagogastroduodenoscopy (EGD) results, age, gender, H. Pylori infection, type of NSAIDs, history of smoking, history of anticoagulants, history of corticosteroids and risk factors for EGD abnormalities in the gastric and duodenal due to NSAIDs use at Sanglah General Hospital in 2016-2018. This study is a retrospective cross-sectional study based on the medical records of patients who underwent endoscopy at Sanglah General Hospital in 2016-2018. The sampling technique was total sampling, then all data were analyzed using bivariate analysis of the chi-square test and multivariate logistic regression analysis. From 92 patients who met the criteria, men (54.3%) and women (45.7%) with the majority of the age group ³ 60 years (95.7%), EGD abnormalities were obtained in the form of superficial gastritis (33.7%), erosival gastritis (28.3%), gastric ulcer (28.3%), duodenal ulcer (5.4%). With ulcer characteristic are Forrest III (90.3%) and  single (74.2%). The majority of patients used non-selective NSAIDs (94.5%), namely ketorolac 30 mg (40.2%). From the biopsy examination, the patient had H. pylori infection (20.5%). Based on medical records, the patients had a history of smoking (59.8%). Patients also found a history of use of anticoagulants (16.3%) and corticosteroids (35.9%). In this study, there was a significant relationship between H. pylori infection and severe EGD abnormalities in NSAID users (P = 0.012). In this study, there were no independent risk factors for severe EGD abnormalities in NSAID users, but there was a significant relationship between H. pylori infection and severe EGD abnormalities in NSAID users Keywords : NSAIDs, EGD, EGD abnormalities in NSAIDs user.